DETERMINANTS OF URBAN POVERTY IN SULAWESI : A PANEL ECONOMETRIC APPROACH, 2015-2024 - Sri Julyarti Halid; Rasman (Institut Agama Islam Negeri (IAIN) Bone, 2026)
Abstract This study aims to analyze the determinants influencing poverty levels in four major cities in Sulawesi—Palu, Manado, Makassar, and Kendari—during the period 2015–2024. The independent variables include the Human Development Index, economic growth, unemployment rate, population size, and inflation. The analytical method employed is a panel data model using the Fixed Effect Model, selected based on the Chow test results with a Prob (F) value of 0.0000 < 0.05. The results show that, simultaneously, socioeconomic variables have a significant effect on poverty levels, with a Prob (F-statistic) value of 0.0000 and an R² of 0.8749, indicating that 87.49% of the variation in poverty is explained by the independent variables in the model. Partially, the Human Development Index has a negative effect on poverty in line with theoretical expectations, while economic growth shows a positive effect that deviates from expectations, indicating that economic growth has not been inclusive. The unemployment rate has a positive effect on poverty as predicted by theory, whereas total population size and inflation have negative but statistically insignificant effects. Keywords: Poverty, Human Development Index, Economic Growth, Unemployment, Inflation